Про підвищення безпеки обміну файлами у відеоконференціях - Філімонов, Д. А.; Антіпов, І. Є. (ХНУРЕ, 2022)
Theses are about the files protecting that are transferred within the videoconference. Onion nesting and file encryption are suggested. According to algorithm, one of the layers contains a mechanism for comparison the real and expected IP-address. In case of a match, the inner protective layer is removed and the file becomes available. If there is a mismatch, the data will be destroyed. The algorithm will make it impossible to intercept attached files from a media stream that is weakly protected.